Tshebediso ya melao kabong ya dinoko tsa Sesotho. Issue 4 (2nd October 2022) - Sibeko, Johannes
Abstract: This article investigates the syllabification of Sesotho words using a rule-based approach. A total of eleven syllabification rules are proposed based on Guma's (1982) three types of syllables, that is, consonant only (C), consonants and vowels (CV), and vowels only (V) syllable types. The syllabification rules are established using the South African Sesotho (SAS) orthography. The proposed syllabification rules are illustrated and applied to an extract from Masowa (2017). The outcomes indicate that the laws of syllabification proposed in this article are sufficient for syllabification of Sesotho words. Among other findings, we differ from Guma (1982) by proposing the removal of the /ny/ consonant digraph from the list of C syllable subtypes. Moreover, we extend Madigoe's (2003) list of CV syllable subtypes by adding two more CV syllable subtypes based on the number of consonants preceding the vowel in CV syllables. These suggested CV subtypes focus on the number of vowels that precede the consonant-vowel syllable types. We believe that if the rules suggested in this article are used correctly, the development of an automated syllabification system for Sesotho can be achieved.